Psycho-diagnostics in a Xhosa Zionist church - Thorpe, Mark Richard (Rhodes University, Faculty of Humanities, Department of Psychology, 1982)
A large number of Black patients seen by the mental health team in South Africa consult indigenous healers. An awareness of the diagnosis and treatment given to patients by traditional healers, would therefore enhance both the rapport with and treatment of those patients who seek help from the mental health professionals and para-professionals.
Keywords: Psychodiagnostics -- South Africa; Xhosa (African people) -- Religion; Xhosa (African people) -- Psychology; Zionist churches (Africa) -- South Africa; Healers -- South Africa; Healing -- South Africa -- Religious aspects